The Circular Circular Economy Development to Achieve Indonesia's SDGs in 2030 in the perspective of Islamic Economics in the Era of society 5.0 - Sanjaya, Vicky F (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
The application of linear economics makes economic actors think about how to get the maximum benefit through activities to explore existing natural resources, with the concept of make, use, and dispose of. The problems of waste, climate change, gas emissions, industrial waste, and water sources require us to switch to a more sustainable economic system. The circular economy is an environmentally friendly economy by maximizes the use of goods over a long period. The type of research in this study is qualitative research, after all the data is collected there is a stage of data credibility test where researchers check and triangulate research data. This study aims to answer the formulation of the problem, namely How is the circular economy development model in the era of society 5.0? What factors affect the success of the circular economy? What is the Islamic view related to the development of the circular economy in the era of Society 5.0? The results show that the development of a circular economy in the era of Society 5.0 can be carried out through the management of cattle waste into fertilizer and biogas. 4 factors influence the success of the circular economy, namely literacy, experience, technology, and financial adoption. The development of circular economy in Islam reflects the value of maslahah which refers to its usefulness and goodness.